Philosophical problems of intellectual culture (Journal of Philosophy Culture and Political Science, 2015)
The paper analyzes the philosophical problems of formation of intellectual culture. Particular attention is paid to the value problem of the relationship of the world practices and traditions in the formation of intellectual culture, studied cultural, historical, social and political aspects. Formation of intellectual culture is considered in a coherent manner the history and content of intellectual culture, most paid to the national spiritual and cultural sources for the growth of intellectual potential, cultural dialogue and interaction. Intellectual traditions are understood as deriving from the basic function of intelligent historical baggage and necessary function of intellectual culture, form and method of preserving the intellectual heritage. Focuses not only on the relationship of ideas and methods of intellectual tradition, continuity and historical heritage, but also an active perception, a new modeling, creative intent, and the introduction of new criticism of their performance. A review on the social problems of education and science.
Keywords: history; philosophy; sociology; modernization; intellectual culture; intelligent Nation; Kazakhstan.